2000
DOI: 10.1128/iai.68.2.732-739.2000
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Immunogenicity of Hemagglutinin A from Porphyromonas gingivalis in an Avirulent Salmonella enterica Serovar Typhimurium Vaccine Strain

Abstract: Porphyromonas gingivalis is a major etiologic agent of periodontitis, a chronic inflammatory disease that ultimately results in the loss of the supporting tissues of the teeth. Previous work has demonstrated the usefulness of avirulent Salmonella enterica serovar Typhimurium strains as antigen delivery systems for protective antigens of pathogens that colonize or cross mucosal surfaces. In this study, we constructed and characterized a recombinant S. enterica serovar Typhimurium avirulent vaccine strain which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…A previous study confirmed by Western immunoblotting that oral immunization with recombinant avirulent Salmonella enterica serovar Typhimurium expressing HagA induces HagAspecific serum antibody responses (30). In addition, a hen egg yolk antibody (IgY) against a truncated HagA protein has been developed (53).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A previous study confirmed by Western immunoblotting that oral immunization with recombinant avirulent Salmonella enterica serovar Typhimurium expressing HagA induces HagAspecific serum antibody responses (30). In addition, a hen egg yolk antibody (IgY) against a truncated HagA protein has been developed (53).…”
Section: Discussionmentioning
confidence: 75%
“…Multiple hemagglutinin genes have been cloned from P. gingivalis by functional screening (35,42,44,49). Among these, hemagglutinin A (HagA) has been thought to contain the functional domain of hemagglutinin and to be a potentially useful immunogen that elicits a protective immune response against subsequent colonization by P. gingivalis (30). The hagA gene is 7,887 bp long and encodes a protein of 2,628 amino acids, with a molecular mass of 283.3 kDa (17).…”
mentioning
confidence: 99%
“…E. coli pEKS5 carries the same insert in expression vector therefore we expect to have similar localization. Based on these data, it was not surprising to observe, using EM, that the (entire) HagA, expressed in S. enterica , was also surface-associated [40]. …”
Section: Discussionmentioning
confidence: 99%
“…A vaccine strain of Salmonella enterica serovar Typhimurium χ4072 ( S. enterica pNM1.1), which expresses the functional hemagglutinin A of P. gingivalis , and it respective control strain harboring an empty vector were described in a previous study and grown in LB broth or plates [40]. A diagram of S. enterica pNM1.1 insert can be found in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation